2009
DOI: 10.1021/ja8089922
|View full text |Cite
|
Sign up to set email alerts
|

Nonvolatile Bipolar Resistive Memory Switching in Single Crystalline NiO Heterostructured Nanowires

Abstract: We have demonstrated the nonvolatile bipolar resistive memory switching in single crystalline NiO heterostructured nanowires for the first time. The self-assembled NiO nanowires are expected to open up opportunities to explore not only the detailed nanoscale mechanisms in NiO resistive memory switching but also next-generation nanoscale nonvolatile memory devices with the potential for high-density device integration and improved memory characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
122
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(127 citation statements)
references
References 29 publications
4
122
1
Order By: Relevance
“…[1][2][3] Utilizing resistive switching between a low-resistance state (LRS) and high-resistance state (HRS), resistive random access memory serves as a potential alternative to the current flash memory for ultrahigh-density storage. Although resistive switching has been observed in various transition metal oxides, [4][5][6][7][8][9][10][11][12][13] the microscopic mechanism is not yet fully understood, which may limit its use in the integrated circuit industry. The primitive filament model 1 provided the first sketch for the conduction mechanism and stimulated later theoretical investigations 5,11,14,15 meant to elucidate various switching phenomena.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Utilizing resistive switching between a low-resistance state (LRS) and high-resistance state (HRS), resistive random access memory serves as a potential alternative to the current flash memory for ultrahigh-density storage. Although resistive switching has been observed in various transition metal oxides, [4][5][6][7][8][9][10][11][12][13] the microscopic mechanism is not yet fully understood, which may limit its use in the integrated circuit industry. The primitive filament model 1 provided the first sketch for the conduction mechanism and stimulated later theoretical investigations 5,11,14,15 meant to elucidate various switching phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…6,20,24 However, most nanowire-based devices exhibit large switching voltages and distributions, 24 which may partly result from the large distance between two electrodes. 12 To overcome these shortcomings, we previously developed multilayered NiO/Pt nanowire arrays with controllable and reproducible resistive transitions.…”
Section: Introductionmentioning
confidence: 99%
“…21 It was also found that bipolar switching from NiO-based devices requires a diÂźerent switching mechanism as the active materials are single crystal NiO in a nanowire structure. 22,23 From our results, the bipolar switching behavior may relate to the electrode material, as we use an Ag-coated AFM tip. The Ag can dissolve into NiO x when positive voltage is applied.…”
Section: -3mentioning
confidence: 80%
“…In order to understand the essence of EPIR, a large variety of EPIR-materials were investigated, including binary oxides NiO [9][10][11] , ZrO 2 [12][13] and HfO 2 [14][15][16] as well as complex oxides such as Pr 1 -x Ca x MnO 3 [17][18] , BiFeO 3 [19][20][21] , and SrTiO 3 [22][23][24] . In terms of description we can roughly categorize them into two groups of redox and defects.…”
Section: Introductionmentioning
confidence: 99%